A Good Quality Filing System and its Documentation: The Right Information Determined the Right Knowledge for Decision-Making - Thye, Kang Eng (Information Management and Business Review, 2014)
An excellent designed information files and its documentation is vitally an important element to assist the right information reaching the right top management for right decision making. Nevertheless, most functional managements do not realized a good quality files documentation design is actually theirs’ responsibility. They are the experts in designing their respective business functional procedures and modeling. It is inappropriate to rely on IT profession alone when comes to designing of business functional procedures. Mini case studies were adopted to let students have a hands-on trial with the new files’ normalization technique with only four rules as proposed to overcome the conventional entity-relationship diagram approach. Target samples were mainly non-IT students. The result shows this new technique offers few benefits that can speed up learning process, easy to understand, and ease of files’ normalization design for non-IT profession. Without an effective data filing system and its documentation applied by each respective functional manager, certainly a quality and right knowledge cannot be generated to assist company in the right, timely, and economic decision-making.